(untitled) (Contemporary Journal of Social Science Review, 2025)
Secularism is one of the foundational pillars of modern Western thought, which emerged in Europe as a reaction against the ecclesiastical oppression of the Middle Ages. This ideology sought to confine religion to the private sphere of human life while liberating human reason from divine authority. Maulana Syed Abul A‘la Maududi identified secularism as fundamentally incompatible with the core tenets of Islam, arguing that it ultimately seeks to replace divine sovereignty (ḥākimiyyat-e-ilāhiyyah) with human sovereignty. According to Sayyed Maududi, secularism represents not merely political doctrine, but a comprehensive intellectual and civilizational paradigm grounded in atheism, materialism, and moral relativism. By excluding divine guidance from the public domain, it inevitably produces moral degeneration, ethical decay, and social disintegration. This study examines how Sayyed Abul A‘la Maududi, through rigorous intellectual reasoning and critical analysis, unveiled the epistemological, ethical, and civilizational contradictions inherent in secularist thought. Sayyed Maududi’s critique extended beyond negation, offering constructive alternatives rooted in Islamic epistemology. Employing an analytical research methodology grounded in a qualitative approach, the study draws upon Sayyed Maududi’s primary writings and scholarly works to explore his critical assessment of the philosophical underpinnings of secularism within both historical and intellectual contexts. Sayyed Maududi presents Islam as a divinely ordained, holistic system of life that guarantees justice, moral integrity, and human prosperity. The research concludes that Sayyed Maududi’s intellectual framework remains profoundly relevant to the contemporary Muslim world, offering a robust moral and philosophical foundation for confronting modern ideological challenges. His thought reaffirms Islam’s comprehensive role as a complete and divinely guided system of life, harmonizing the spiritual, ethical, and social dimensions of human existence.